Navigating Language Anxiety: Social and Cultural Influences on Javanese Female Students in Learning English - Permatasari, Amaliya Indah; Yannuar, Nurenzia; Eliyanah, Evi (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study explores the English language anxiety experienced by Javanese postgraduate female students. It highlights the influence of social, cultural, and gender factors on language anxiety. Using a qualitative approach with thematic analysis, data were collected through semi-structured interviews with a total of seven students from the English Language Education postgraduate program at Universitas Negeri Malang. The results indicate that there are three main sources of language anxiety: fear of making mistakes due to a culture of shyness, anxiety when speaking in public due to a culture of avoiding confrontation, and lack of preparation in using English in academic contexts. Moreover, Javanese cultural values such as etiquette (tata krama), politeness, harmony (rukun), and gender roles emphasizing politeness have been shown to influence female students' anxiety in using English. Students also used and shared various strategies to cope with anxiety, such as building self-confidence, maintaining a positive mindset, continuing to practice, and creating a comfortable learning environment. This study also highlights the importance of a learning approach that is aware of students' cultural backgrounds in creating a more inclusive and supportive learning environment, such as avoiding negative judgment and monotonous learning.